A second reckoning : race, injustice, and the last hanging in Annapolis - Seligman, Scott D. (Potomac Books, an imprint of the University of Nebraska Press, 2021)
A Second Reckoning tells the story of the 1917 murder that led to the last hanging in Annapolis, Maryland, and makes an appeal for posthumous justice, especially where racial prejudice may have tainted a case.